Digestibility of low-cost ingredients in pelleted feed by grass carp (Ctenopharyngodon idella C. et V.) - Law, A.T. (Elsevier, 1986)
The digestion coefficients of nutrients in 37% protein MARDI feed as well as in napier and carpet grass meals were evaluated in grass carp. Cr2O3 was used as an internal marker for the evaluation of digestibility. In the MARDI feed, the fish meal and soya bean meal were digested most by the fish: the digestion coefficients for protein were 90.81% and 96.21%, respectively; for fat the values were 100% and 98.79%, respectively; and for gross energy the values were 83.37% and 82.71%, respectively. These results indicate that it may be feasible to replace fish meal partially with soya bean meal in the MARDI feed for grass carp. The digestion coefficients for dry matter and carbohydrate of maize were 64.76% and 87.85%, respectively, although protein, fat and gross energy in maize were poorly utilized by the fish. Copra cake and rice bran were poorly digested by the fish. These two ingredients should be deleted in feed formulations for this fish.